PENGARUH SKALA USAHA, UMUR USAHA, BUDAYA ORGANISASI DAN PELATIHAN PENYUSUNAN LAPORAN KEUANGAN TERHADAP IMPLEMENTASI STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABITAS PUBLIK (SAK ETAP) - Titu, Yovita; Soleiman, Iriany Dewi; Londa, Yulita (Program Studi Akuntansi Universitas Flores, 2022)
The purpose of this study was to determine the effect of Business Scale, Age of Business, Organizational Culture and Financial Reporting Training on the Implementation of Financial Accounting Standards for Entities Without Public Accountability (Sak Etap) (Empirical Study on Cooperatives in Ende Regency). Based on the purposive technique, this study used a sample of 36 respondents. The type of research used is quantitative. This study uses primary data, namely questionnaires. Data were analyzed using multiple linear regression analysis which processing through IBM SPSS Statistics ver 25. The results of this study indicate that: (1) Business Scale has an effect on the implementation of SAK ETAP. This is evidenced by the regression coefficient value of the Business Scale variable of 0.449 with tcount > ttable (2.205 > 2.040) and a significant level of 0.035 <0.05. (2) Age of Business affects the Implementation of SAK ETAP. This is evidenced by the regression coefficient value of the Age of Business variable of 0.885 with tcount > ttable (3.076 > 2.040) and a significant level of 0.004 <0.05. (3) Organizational Culture influences the implementation of SAK ETAP. This is evidenced by the regression coefficient value of the Organizational Culture variable of 0.765 with tcount > ttable (4.690>2.040) and a significant level of 0.000<0.05. (4) Financial Report Preparation Training has an effect on the Implementation of SAK ETAP. This is evidenced by the regression coefficient value of the Financial Statement Preparation Training variable of 0.560 with tcount > ttable (5.809>2.040) and a significant level of 0.000 <0.05. Simultaneously, the variable of SAK ETAP implementation is influenced by the variables of Business Scale, Age of Business, Organizational Culture, and Training on Financial Reporting by 59.8%. While the remaining 40.2% is explained by other variables outside the model.